3D-seismic interpretation of the glacial deposits in the outer Ingøydjupet area, SW Barents Sea. Ice sheet dynamics reconstructed from glacial landforms - Strømme, Kristine (UiT Norges arktiske universitet, 2019)
The late Quaternary evolution of the outer Ingøydjupet area (SW Barents Sea) is studied using a merge of conventional 3D-seismic cubes and a new generation of high-resolution 3D-seismic (TopSeis). The glacigenic sequence is subdivided into five main seismic units: unit A1 (oldest) to A5. These are separated by six glacially eroded boundaries: the Upper Regional Unconformity (URU), intra-glacial horizons (Q1-Q4) and the seafloor. A correlation to established seismic stratigraphies suggests that the units A1-A3 were deposited during middle Pleistocene and A4-A5 during late Pleistocene. The internal seismic signature of the units is described and the geomorphologies of the main surfaces are mapped. This forms the basis for a reconstruction of the ice-sheet dynamics and depositional environment during the late Quaternary evolution of the outer Ingøydjupet area. Mega-scale glacial lineations and troughs observed on the paleo-surfaces confirm that fast-flowing ice streams have occupied and eroded the outer Ingøydjupet area at least five times since the formation of the URU. The orientation of the lineations suggests that both the Ingøydjupet- and the Bjørnøyrenna Ice Streams have been active in the area during these glaciations. Buried sediment blocks, which are interpreted to have been entrained, transported and re-deposited by the paleo-ice streams indicate that the ice streams underwent phases of basal freezing. The recessional features on the URU and the seafloor suggest complex and dynamic retreats of the ice sheet following glacial maxima, where repeated halts and re-advances characterized the deglaciation. The intra-glacial horizons on the other hand show evidence of rather rapid ice sheet retreats, where mega-scale glacial lineations are preserved on the paleo-surfaces.